2015
DOI: 10.1590/1981-863720150002000132564
|View full text |Cite
|
Sign up to set email alerts
|

Dens invaginatus: case report

Abstract: Dens invaginatus is one of the most frequent malformations in dental elements. It can affect all teeth, even primary and supernumerary ones. It consists of an invagination of the crown surface, which happens during odontogenesis and penetrates the interior of the pulp chamber of the dental elements involved. In some cases, it can reach the apical tooth area. The maxillary lateral incisor is the most common site of occurrence. Due to its complex and variable anatomy, the tooth may present pulp necrosis and open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…28 Such teeth often present thin and fragile root walls and wide apex, and it is critically important to maintain these teeth as long as possible, especially in young patients, to maintain the space until occlusion is established. 29 In the present case, root canal treatment with proper chemical and mechanical preparation of the main root canal and dens invaginatus in combination with removal of the cyst lining and the biodentine retrograde filling resulted in regression of the periapical pathology with adequate healing at recall visits.…”
Section: Discussionmentioning
confidence: 58%
“…28 Such teeth often present thin and fragile root walls and wide apex, and it is critically important to maintain these teeth as long as possible, especially in young patients, to maintain the space until occlusion is established. 29 In the present case, root canal treatment with proper chemical and mechanical preparation of the main root canal and dens invaginatus in combination with removal of the cyst lining and the biodentine retrograde filling resulted in regression of the periapical pathology with adequate healing at recall visits.…”
Section: Discussionmentioning
confidence: 58%
“…The invagination was lined with Calcium Hydroxide to stimulate formation of secondary dentin and Conventional glass ionomer cement was used to provide secondary caries inhibition. Lucas, et al (2003) [24] showed that regular follow-up and periodic evaluation are necessary after an early prophylactic sealing of type II invagination since it appears not to be always favorable.…”
Section: Discussionmentioning
confidence: 99%